Pelaksanaan Good Corporate Governance (GCG) dalam Perseroan Terbatas (Lex Jurnalica, 2009)
Good Corporate Governance (GCG) is importance for company. With applications GCG, management company will walk efficient and effective, so that affect in, that is: big the so small profit that be got to company, big not it risk that be undergone to company that can evoke loss, well guaranted not it effective production in companies,Â  and to watch over continuity effort. Wri-ting method that used juridical normatif, as to data collecting technique is got from literature watchfulness. As to principles gcg, that is justice principle (justice), transparancy, accountability, responsibility, independency, equivalence and spontanity (fairness), while execution good corpo-rate governance (gcg), decision making system follows gcg in limited liability, conflict of interest stockholder, commissioner,Â  and management.Keywords: Good Corporate Governance, Management Company, Principles